'Nordicness' in Swedish foreign policy – from mid power internationalism to small state balancing?. Issue 4 (20th October 2018) - Brommesson, Douglas
ABSTRACT: This paper focuses on Nordicness, i.e. the perception and recognition of a Nordic role in Swedish foreign policy. Based on a framework about security cultures, it identifies and analyses Nordicness – defined in terms of role perceptions – in Swedish foreign and security policy. The analysis identifies three roles: internationalist leader during the period of active foreign policy in the latter part of the Cold War, Europeanized follower during the height of reorientation towards the EU and today's Nordic balancer. The analysis reveals how Nordicness recently began re-appearing in a security environment characterized by increasing levels of tension. Compared to the Cold War period, shared Nordic norms and identity are less apparent today. Instead, the material security environment has become increasingly important. Recent increases in Nordicness in Swedish foreign policy have taken place in the context of a tenser security situation and have been associated with national security rather than a shared mission of internationalism. The article concludes that, in addition to internationalism, Nordicness has become a source of considerably more materialistic concerns.